Investigation of membrane fouling in an anaerobic membrane bioreactor (AnMBR) treating pharmaceutical wastewater - Kaya, Yasemin; Bacaksiz, Ahmet Murat; Bayrak, Hasan; Vergili, Ilda; Gonder, Zeren Beril; Hasar, Halil; Yilmaz, Gulsum (Elsevier, 2019)
This study is focused on the fouling of flat-sheet and hollow-fiber membranes in a lab-scale anaerobic membrane bioreactor (AnMBR). A comprehensive investigation including scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDX), fourier transform infrared (FT-IR) spectroscopy, confocal laser scanning microscopy (CLSM), zeta potential, optical profilometer and contact angle, and flux modelling was presented in this study. The effect of extracellular polymeric substances (EPS) accumulated on cake-layer were also considered. The cake-layer on the flat-sheet membrane formed much more than that on the hollow-fiber membrane. The thickness of cake-layer on the flat-sheet membrane was effectively decreased by physical stripping. However, proteins indicating structures of Amide I and Amide II, and carbohydrates were observed on the stripped hollow-fiber membrane. According to the flux modelling results, the cake-layer formation and intermediate-adsorption were found as effective mechanisms on both membranes. Especially, these mechanisms were more effective for the hollow-fiber membrane due to irreversible fouling.
Keywords: Anaerobic membrane bioreactor; Flat-sheet membrane; Hollow-fiber membrane; Membrane autopsy; Flux modelling